Highly transparent, low sheet resistance and stable Tannic acid modified-SWCNT/AgNW double-layer conductive network for organic light emitting diodes. (9th October 2020) - Zhu, Ze-Ru; Geng, Wenming; Zhu, Qingxia; Ethiraj, Anita Sagadevan; Wang, Tao; Jing, Li-Chao; Ning, Yu-Jie; Tian, Yi; Geng, Wen-Hao; Wu, Lei; Geng, Hong-Zhang
Abstract: In this paper, we used tannic acid (TA) functionalized carbon nanotubes (TCNTs), and silver nanowires (AgNWs) to construct a new type of transparent conductive film (TCF) with a double-layered conductive network structure. The hybrid film exhibits excellent light transmittance, high electrical conductivity, ultra-flexibility, and strong adhesion. These outstanding performances benefit from the filling and adhesion of hydrophilic TCNT layers to the AgNW networks. Besides, we introduced the post-treatment process of mechanical pressing and covering polymer conductive polymer PEDOT:PSS, which obtained three layers of TCNT/AgNW/PEDOT hybrid film and greatly improved the comprehensive properties. The hybrid film can reach a sheet resistance of 9.2 Ω sq −1 with a transmittance of 83.4% at 550 nm wavelength, and a low root mean square (RMS) roughness (approximately 3.8 nm). After 10 000 bends and tape testing, the conductivity and transmittance of the hybrid film remain stable. The resistance of the film has no significant degradation after 14 d of exposure to high temperature of 85 °C and humidity of 85%, indicating excellent stability. The organic light-emitting diodes (OLEDs) with TCNT/AgNW/PEDOT hybrid film as anode exhibit high current density and luminosity, confirming this process has considerable potential application in photovoltaic devices.